2016
DOI: 10.1111/nyas.13041
|View full text |Cite
|
Sign up to set email alerts
|

Management of beta‐thalassemia–associated osteoporosis

Abstract: Beta-Thalassemia-associated osteoporosis is a multifactorial and complex condition. Different acquired and genetic factors are involved in its pathogenesis. These factors produce an imbalance in bone remodeling by inhibiting osteoblast activity and increasing osteoclast function, leading to bone loss and increased fracture risk. The management of patients presenting with thalassemia-associated osteoporosis should consist of the implementation of general measures and the prescription of a specific pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 61 publications
0
33
0
1
Order By: Relevance
“…Subclinical microfractures, particularly throughout the vertebral column, are now recognized as an increasing problem in this population . Recently, atypical femoral fracture as a result of long‐term bisphosphonate use was observed for the first time in thalassemia …”
Section: Low Bone Massmentioning
confidence: 99%
“…Subclinical microfractures, particularly throughout the vertebral column, are now recognized as an increasing problem in this population . Recently, atypical femoral fracture as a result of long‐term bisphosphonate use was observed for the first time in thalassemia …”
Section: Low Bone Massmentioning
confidence: 99%
“…The pathogenesis of thalassemia-related osteoporosis is multifactorial and dependent on genetic variants, bone marrow expansion, iron burden, iron chelators, renal involvement, and endocrine condition; therefore, osteoporosis management is difficult in these patients ( 11 ). This study showed that single-dose zoledronic acid therapy over a year (4-mg, single dose once yearly) was effective in improving lumbar spine BMD in the treatment of osteoporosis in patients with thalassemia.…”
Section: Discussionmentioning
confidence: 99%
“…Zoledronic acid is a potent inhibitor of bone resorption, and likely improves bone density through direct inhibition of osteoclasts by interfering with protein prenylation ( 10 ). Zoledronic acid has been tested with different dosing regimens (4 mg IV every 3 months or 4 mg IV every 6 months) for osteoporosis management in thalassemia patients ( 11 ). Zoledronic acid 4 mg IV every 3 months is one of the most promising protocols ( 8 - 9 , 12 ) but evidence is lacking with respect to other potential doses (such as IV zoledronic acid administered annually) for the treatment of low BMD associated with thalassemia ( 13 - 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thalassemia-associated osteoporosis is among the most commonly observed complications of the disease seen as a result of various factors such as hypogonadism, delayed puberty, bone marrow expansion, iron overload, desferrioxamine (DFO) toxicity, genetic factors, calcium, Vitamin D and GH /IGF-1 deficiencies, hypoparathyroidism, hypothyroidism and decreased physical activity 1,2,3,4,5 . Severity of the bone disease in thalassemia is associated with the underlying type of thalassemia and its treatment.…”
Section: Introductionmentioning
confidence: 99%